"I know it when I see it": employing reflective practice for assessment and feedback of reflective writing in a makerspace classroom. Issue 3 (19th May 2021) - Chen, Ofer; Bergner, Yoav
Abstract : Purpose: In reflective writing, students are encouraged to examine their own setbacks and progress. With a shortage of guidance in how to provide feedback to students on this type of writing, teachers are often left to figure it out on the job. The central hypothesis in this paper is that the lens of reflective practice can help focus teacher efforts and ultimately improve both feedback and instruction. The purpose of this paper is not to produce a universal prescription for assessing reflective writing but rather a protocol for teacher reflective practice that can apply to challenging grading and feedback-giving situations. Design/methodology/approach: Student assessment is a chance for teachers to learn about their students' abilities and challenges and to provide feedback for improvement. Assessment and grading sessions can also become opportunities for teachers to examine their own instructional and assessment practices. This self-examination process, a cornerstone of reflective practice (Schön, 1984 ), is challenging, but it may be especially valuable when guidelines for feedback and assessment are hard to come by. Such may be said to be the case in student-centered learning environments such as school Fablabs and makerspaces, where stated goals commonly include cultivating learner self-regulation and resilience. These hard-to-measure constructs are typically assessed through analysis of student reflective journals. This in-depth case study uses mixed-methods to examine how a semester-long intervention affected the grading, feedback and instructional practices of a teacher in a hands-on design classroom. The intervention involved 10 grade-aloud sessions using a computer-based rubric tool (Gradescope) and a culminating card-sorting task. The lens of reflective practice was applied to understanding the teacher's development of their own reflective capabilities. Findings: During the intervention, the participating teacher grappled with grading and feedback-giving dilemmas which led to clarifications of assessment objectives; changes to instruction; and improved feedback-giving practices, many of which persisted after the intervention. The teacher perceived the intervention as adding both rigor and productive "soul-searching" to their professional practice. Lasting changes in feedback behaviors included a comprehensive rubric and an increase in the frequency, specificity and depth of feedback given to student written work. Originality/value: Significant prior efforts have been directed separately at the use of reflective practice for teachers, in general, and on the feedback and grading of student process journals. This work combines these lines of inquiry in the reflective classroom assessment protocol, a novel on-the-job professional development opportunity that fosters reflective practice in times of assessment to improve instructional and feedback practices.